2009
DOI: 10.3816/clm.2009.n.042
|View full text |Cite
|
Sign up to set email alerts
|

Hodgkin Lymphoma: An Update on its Biology with New Insights into Classification

Abstract: In the last few years, there has been a greater understanding of the spectrum and biology of Hodgkin lymphoma. In standard texts, Hodgkin lymphoma is classified as two distinct entities, namely nodular lymphocyte predominant Hodgkin lymphoma and classical Hodgkin lymphoma. However, recent evidence suggests that classical Hodgkin lymphoma is not a single disease. While the mixed cellularity and lymphocyte depleted subtypes may be part of a biologic continuum, the nodular sclerosis subtype has a distinct epidemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
89
1
13

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(107 citation statements)
references
References 186 publications
4
89
1
13
Order By: Relevance
“…Alternatively, other studies suggested that the induction of major histocompatibility complex class I and II expression on hair follicles may lead to the activation of CD8 + T-lymphocytes towards hair follicle melanocytes and recruitment of CD4 + T-lymphocytes that further attack the hair follicles, a process that may be perpetuated and amplified by the clonal T-cell proliferation seen in lymphomas (4). There is also a genetic predisposition contributing to such phenomena, given the numerous human leukocyte antigen subtypes shared by AA and HL (1,10). The resolution of AA observed with the remission of HL in our patient and other case reports reaffirms the close association between these two conditions.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Alternatively, other studies suggested that the induction of major histocompatibility complex class I and II expression on hair follicles may lead to the activation of CD8 + T-lymphocytes towards hair follicle melanocytes and recruitment of CD4 + T-lymphocytes that further attack the hair follicles, a process that may be perpetuated and amplified by the clonal T-cell proliferation seen in lymphomas (4). There is also a genetic predisposition contributing to such phenomena, given the numerous human leukocyte antigen subtypes shared by AA and HL (1,10). The resolution of AA observed with the remission of HL in our patient and other case reports reaffirms the close association between these two conditions.…”
Section: Discussionsupporting
confidence: 67%
“…AA, however, as a paraneoplastic syndrome of Hodgkin's lymphoma (HL), remains limited to a few case studies, although its occurrence in HL was anecdotally referenced in the early 1900s (6)(7)(8)(9). The etiology of AA as a paraneoplastic syndrome of HL remains unknown, although it was considered to be a T-lymphocyte-mediated phenomenon involving production of cytokines, initiation of the inflammatory cascade and genetic predisposition (1,4,8,10).…”
Section: Introductionmentioning
confidence: 99%
“…While most other subtypes of CHL occur in the peripheral lymph nodes with an apparent male predominance, NSCHL most commonly occurs in the mediastinal region with a roughly 1:1 male to female ratio. Compare to other subtypes, NSCHL is also less likely to be associated with EBV (20%) [24,25]. Accumulating evidence has demonstrated a close link between NSCHL and DLBCL.…”
Section: Issn: 2377-9292mentioning
confidence: 99%
“…cHL represents nearly 95% of HLs. [1][2][3] cHL has a relatively good prognosis and with current chemotherapeutic and radiotherapeutic regimens, patients cure can be achieved in 80% of cases. The remaining 20%, patients may be refractory to primary treatment or show relapse after remission.…”
Section: Introductionmentioning
confidence: 99%